Masks, Face Veil Bans and “Living Together”: What’s Privacy Got to Do with It? - Kahn, Robert (Public Governance, Administration and Finances Law Review, 2022)
The “living together” concept poses a puzzle. Why did Europeans decide that life in a modern democracy requires showing one’s face? One explanation is opposition to Muslims and Islam. But the enforcement of face veil bans against non-religious mask wearing raises doubts. This essay poses an alternative explanation. What if the face veil bans persist because of European conceptions of privacy? Von Hannover v. Germany held that one be private in public. Given this, why wear a mask? What is there to hide? To explore this idea, the essay turns to the United States, where one cannot be “private in public” and mask wearing has been opposed on narrow grounds such as public security and the content of specific masks. At the same time, the United States respects the decisional privacy of someone to wear a mask even for “irrational” reasons, something the “living together” idea tends to ignore.